Observing prosociality and talent: the emotional characteristics and behavioral outcomes of elevation and admiration in 6.5- to 8.5-year-old children - Gibhardt, Sina; Hepach, Robert; Henderson, Annette M. E. (Frontiers in Psychology, 2024)
Helping and seeing others being helped elicits positive emotions in young children but little is known about the nature of these emotions, especially in middle childhood. Here we examined the specific emotional characteristics and behavioral outcomes of two closely related other-praising moral emotions: elevation and admiration. We exposed 182 6.5- to 8.5-year-old children living in New Zealand, to an elevation- and admiration-inducing video clip. Afterwards children’s emotion experiences and prosocial behaviour was measured. Findings revealed higher levels of happiness, care, and warmth after seeing prosociality in others (elevation condition) and higher levels of upliftment after seeing talent in others (admiration condition). We found no differences in prosocial behavior between the elevation and admiration conditions. This is the first study to assess elevation in childhood and offers a novel paradigm to investigate the role of moral emotions as potential motivators underlying helping.